Changes in structure, rheological property and antioxidant activity of soy protein isolate fibrils by ultrasound pretreatment and EGCG. (January 2022) - Tong, Xiaohong; Cao, Jia; Tian, Tian; Lyu, Bo; Miao, Liming; Lian, Ziteng; Cui, Wenyu; Liu, Shi; Wang, Huan; Jiang, Lianzhou
Abstract: Impacts of ultrasound pretreatment on the formation of soy protein fibrils, interaction of soy protein fibrils and EGCG, rheological property and antioxidant activity of the complex, and bioaccessibility of EGCG were investigated in this study. Fourier-transform infrared (FTIR) spectroscopy, fluorescence spectroscopy, and surface hydrophobicity (H0 ) indicated that ultrasound caused the unfolding of soy protein structure and exposure of hydrophobic regions. Compared with the un-treated soy protein fibrils, there were greater Thioflavin T fluorescence intensity and β-sheet content in the ultrasound-treated protein fibrils. These results indicated that ultrasound pretreatment could be used for modifying soy protein to improve its fibrils formation. FTIR spectroscopy, fluorescence spectroscopy, X-ray diffraction, and H0 showed that protein fibrils mainly interacted with EGCG through hydrogen bonds and hydrophobic interactions. The stability, viscosity, and antioxidant activity of soy protein fibrils treated with ultrasound-assisted EGCG (U–F-EGCG) were greater than those of other samples. EGCG drove the formation of protein fibrils-EGCG hydrogels. In vitro bioaccessibility of EGCG was significantly improved after its formation of complex with protein fibrils. Hence, the soy protein fibril hydrogels system can extend the application as the delivery carriers of bioactive compounds. Graphical abstract: Image 1 Highlights: Ultrasound pretreatment affected the formation of soy protein fibrils. Protein fibrils interacted with EGCG by hydrogen bonds and hydrophobic interactions. Protein fibrils treated by ultrasound and EGCG had the highest antioxidant activity. EGCG bioaccessibility was increased in the presence of protein fibrils.